2018
DOI: 10.15562/phpma.v6i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis B virus infections among pregnant women in East Lombok District

Abstract: Background and objectives: The World Health Organization has set a target of 90% reduction in new Hepatitis B infections by 2030. The program includes prevention of new infections, and increases testing uptake and treatment. In order to effectively foster prevention, it is necessary to understand the risk factors for transmission. This study aims to determine the risk factors of Hepatitis B infection in pregnant women.Method: A case control study was carried out among 52 pregnant women with HBsAg (+) as cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
1
1
1
7
Order By: Relevance
“…Age variable were statistically significant related to the incidence of hepatitis B virus infection in pregnancy with a p value of 0.000 and OR 0.244 meaning that pregnant women aged <16 and > 40 years 76% were spared Hepatitis B virus infection than pregnant women aged 16-40 years. The results of this study are in line with research in (Lombok) reported 63.4% of pregnant women with HBV aged 25-34 years (Faizaturrahmi et al, 2018) The results of this study are in line with several studies in various countries, including research in China which states that the age of mothers who experience the most hepatitis B is 247 people (5.64%) at the age> 20 years and at 4.54 times the risk of being infected with HBV compared to mothers at age <20 year (Ding et al, 2013). At United States, 4391 pregnant women with unknown hepatitis occurred at the age of the group, namely 2572 (59%) in the 26-25 year age group, 1038 (24%) aged ≤ 25 years and 781 (18%) aged> 35 years (Bajema et al, 2018).…”
Section: B Corelated Age With Hepatitis B Virus Infection In Pregnansupporting
confidence: 92%
See 2 more Smart Citations
“…Age variable were statistically significant related to the incidence of hepatitis B virus infection in pregnancy with a p value of 0.000 and OR 0.244 meaning that pregnant women aged <16 and > 40 years 76% were spared Hepatitis B virus infection than pregnant women aged 16-40 years. The results of this study are in line with research in (Lombok) reported 63.4% of pregnant women with HBV aged 25-34 years (Faizaturrahmi et al, 2018) The results of this study are in line with several studies in various countries, including research in China which states that the age of mothers who experience the most hepatitis B is 247 people (5.64%) at the age> 20 years and at 4.54 times the risk of being infected with HBV compared to mothers at age <20 year (Ding et al, 2013). At United States, 4391 pregnant women with unknown hepatitis occurred at the age of the group, namely 2572 (59%) in the 26-25 year age group, 1038 (24%) aged ≤ 25 years and 781 (18%) aged> 35 years (Bajema et al, 2018).…”
Section: B Corelated Age With Hepatitis B Virus Infection In Pregnansupporting
confidence: 92%
“…This result is not in line with a study in Iran that found 5.72% of HBV cases in pregnant women with a previous abortion risk (Afzali et al, 2015), a study in China of 15 women with a history of previous abortions ≥ 2 times. (Cui et al, 2016) As well as research in Indonesia (East Lombok) which found 17.3% of mothers infected with HBV had had an abortion (Faizaturrahmi et al, 2018). The results of this study are not in line with the 2015 Noubiap study which stated that blood transfusion is one of the variables associated with HBV infection (Noubiap et al, 2015).…”
Section: F Corelated Gestitional Age With Hepatitis B Infectioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Penelitian ini memiliki hasil yang serupa dengan penelitian Surapathi (21) di Karangasem, Bali, di mana ibu yang menikah di bawah usia 19 tahun berisiko 2,5 kali terinfeksi hepatitis B dibandingkan ibu yang menikah di atas usia 19 tahun dengan p value sebesar 0,024. Begitu juga dengan penelitian Faizaturrahmi (22) di Kabupaten Lombok Timur yang menemukan bahwa ibu yang menikah pada usia kurang dari 19 tahun berisiko 2,3 kali lebih besar terinfeksi hepatitis B dibandingkan dengan responden yang menikah lebih dari 19 tahun dengan p value sebesar 0,02. Usia pernikahan juga berhubungan dengan tingkat pendidikan mereka, semakin dewasa usia saat pertama menikah, maka semakin tinggi tingkat pendidikannya, begitu juga sebaliknya.…”
Section: Hubungan Usia Saat Pertama Kali Menikah Dengan Kejadian Hepa...unclassified
“…Perempuan yang menikah di usia dini kurang mampu menegosiasikan seks yang aman, sehingga menyebabkan meningkatnya kerentanan terhadap penyakit menular seksual. Ditambah dengan tingkat pendidikan yang rendah yang menyebabkan pengetahuan yang rendah mengenai kesehatan reproduksi (22).…”
Section: Hubungan Usia Saat Pertama Kali Menikah Dengan Kejadian Hepa...unclassified